LAYANAN APLIKASI GO-JEK: VALIDASI SKALA PENGUKURAN IRSQ PERSEPSI KONSUMEN PADA PENGGUNAAN PLATFORM GO-FOOD - Suryaningsih, Ika Barokah (BISMA: Jurnal Bisnis dan Manajemen, 2019)
This study aims to analyze the factors forming consumers' perceptions in using the Go-food platform at Go-jek application by adopting an IRSQ measurement scale. This study examined 20 attributes of IRSQ that were analyzed using EFA. The population of this study was the citizens of Jember who have used the Go-food platform at Go-jek application. The sample consisted of 140 respondents collected by employing a purposive sampling technique. The results showed that there were 5 factors forming consumers' perceptions of using the Go-Food platform. The most dominant factor was services performance consisting of the attributes of easy-to-understand online order, fast order confirmation messages, fast loading time, error-free order processing, fast order delivery, and order return policies. The second factor was ease of access consisting of the attributes of various products offering by Go-jek’s partners, promotional products offer, recommendations for the unique products, and various payment methods. The third factor was interaction consisting of the attributes of online chatrooms, product images, and communication interactions. The fourth factor was information that consists of the attributes of product availability information and accuracy of the information, while the fifth factor was security that consists of the attributes of personal information and secure account information.